The Relationship between Civil Society Organization and Political Party in Legislative Election: The Case of of Fatayat and PKB in Indonesia - Mahfudhi, M. Anas; Perdana, Aditya (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This article aims to analyze the political strategies of Fatayat as a civil society organization to win women candidates in the 2019 legislative elections. To do so, it uses two concepts of Gwendolyn Bevisâ€™s theory of civil society and political parties which emphasizes constructive relationships between civil society organizations and political parties, and Peter Schroderâ€™s theory on political strategies and tactics to win female candidates of legislative elections. This article uses a qualitative method and collects the data through interview techniques. The result of this study indicates that the relationship between Fatayat and PKB (Partai Kebangkitan Bangsa) runs constructively for both have a shared history. This constructive relationship can also be applied to explain the political dynamic within Nahdlatul Ulama (NU). This article concludes that the Fatayatâ€™s strategy to win women candidates in the legislative elections was supported by a constructive relationship between Fatayat and PKB.Â This finding contributes to the study of the relationship between civil society organizations and political parties.Â